The creative impulse : - Sporre, Dennis J (Prentice Hall, 2000)
This book chronologically introduces the arts of the Western tradition - painting and sculpture, architecture, theatre, music, dance, literature and film - within the context of the philosophy, religion, aesthetic theory, economics and politics that inform them.